2019
DOI: 10.1021/acs.joc.9b01920
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 7′-Arylidenespiro[indoline-3,1′-pyrrolizines] and 7′-Arylidenespiro[indene-2,1′-pyrrolizines] via [3 + 2] Cycloaddition and β-C–H Functionalized Pyrrolidine

Abstract: The acetic acid catalyzed three-component reaction of pyrrolidine, aromatic aldehydes, and 3-arylideneoxindolin-2-ones in refluxing toluene afforded functionalized 7′arylidenespiro[indoline-3,1′-pyrrolizines] in good yields and with high diastereoselectivity. The similar three-component reaction with 2-arylidene-1,3-indanediones also gave 7′arylidenespiro[indene-2,1′-pyrrolizines] in good yields. However, the reaction with 3-phenacylideneoxindoles resulted in a mixture of spiro[indoline-3,1′-pyrrolizines] and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 77 publications
0
12
0
Order By: Relevance
“…According to the previously established reaction conditions for the 7′‐arylidenespiro[indoline‐3,1′‐pyrrolizines], [12g] a mixture of pyrrolidine, benzaldehyde, and 4‐benzylidene‐5‐methyl‐2‐phenylpyrazol‐3‐one was refluxed in toluene in the presence of acetic acid for about sixteen hours. TLC monitoring showed that the reaction resulted in a major product with several byproducts in very low yields.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the previously established reaction conditions for the 7′‐arylidenespiro[indoline‐3,1′‐pyrrolizines], [12g] a mixture of pyrrolidine, benzaldehyde, and 4‐benzylidene‐5‐methyl‐2‐phenylpyrazol‐3‐one was refluxed in toluene in the presence of acetic acid for about sixteen hours. TLC monitoring showed that the reaction resulted in a major product with several byproducts in very low yields.…”
Section: Resultsmentioning
confidence: 99%
“…Very recently, we also reported the domino generation of conjugated azomethine ylides between pyrrolidine and aromatic aldehydes and [3+2] cycloaddition reaction with 3‐arylideneoxindoline‐2‐ones or 2‐arylidene‐1,3‐indanediones for convenient synthesis of novel functionalized spiropyrrolidine derivatives [12g] . In order to further develop the synthetic values of the conjugated azomethine ylides and with our continuous object on developing efficient synthetic methods for heterocyclic spiro compounds, [13] herein we wish to report the three‐component reactions of pyrrolidine, aromatic aldehydes and various cyclic dipolarophiles such as 4‐arylidene‐5‐methyl‐2‐phenylpyrazol‐3‐ones, 2‐arylidene‐ N,N’ ‐dimethylbarbiturates and N ‐phenylmaleimide for the synthesis of diverse spiropyrrolidine and pyrrolo[3,4‐ a ]pyrrolizine derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…The reaction mechanism included β‐C−H functionalization of pyrrolidine, generation of the azomethine ylide intermediate and subsequent 1,3‐dipolar cycloaddition (Scheme 5). [44] The resulting spirooxindole derivatives were investigated by evaluation against mouse colon cancer cells CT26 and human liver cancer cells HepG2 by MTT assay.…”
Section: Cycloadditions To 3‐alkylidene‐2‐oxindoles – A‐type Dipolaromentioning
confidence: 99%
“…In 2019-2020, Yan and co-workers reported transformations resembling reactions shown in Scheme 76, with the modification that N-methylmaleimide is replaced by other electron-deficient alkenes. 133,134 Several other research groups have reported condensation-based reactions involving the -C-H bond functionalization of cyclic amines. Wu, Wu, and co-workers reported a process in which a mixture of pyrrolidine, an -ketoaldehyde, and an acrylate undergo a reaction that leads to simultaneous -and -C-H bond functionalization of the amine to furnish bicyclic 2,3-dihydro-1H-pyrrolizines 166 (Scheme 78).…”
Section: Review Synthesismentioning
confidence: 99%